2019
DOI: 10.3389/fonc.2019.00379
|View full text |Cite
|
Sign up to set email alerts
|

Novel Prognostic Markers in Triple-Negative Breast Cancer Discovered by MALDI-Mass Spectrometry Imaging

Abstract: There are no widely-accepted prognostic markers currently available to predict outcomes in patients with triple-negative breast cancer (TNBC), and no targeted therapies with confirmed benefit. We have used MALDI mass spectrometry imaging (MSI) of tryptic peptides to compare regions of cancer and benign tissue in 10 formalin-fixed, paraffin-embedded sections of TNBC tumors. Proteins were identified by reference to a peptide library constructed by LC-MALDI-MS/MS analyses of the same tissues. The prognostic signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 49 publications
1
31
0
Order By: Relevance
“…The protein product of the COL1A1 gene forms part of the type I collagen protein complex, which has previously been identified as up-regulated in mesenchymal MpBCs when compared to adjacent normal tissue [27]. Further, high expression of the COL1A1 gene and protein has been associated with shorter recurrence free and overall survival in breast cancer, as well as with response to cisplatin [28, 29]. Additionally, we identified increased HAS2 in MpBC samples.…”
Section: Discussionsupporting
confidence: 53%
“…The protein product of the COL1A1 gene forms part of the type I collagen protein complex, which has previously been identified as up-regulated in mesenchymal MpBCs when compared to adjacent normal tissue [27]. Further, high expression of the COL1A1 gene and protein has been associated with shorter recurrence free and overall survival in breast cancer, as well as with response to cisplatin [28, 29]. Additionally, we identified increased HAS2 in MpBC samples.…”
Section: Discussionsupporting
confidence: 53%
“…4 It has recently been used in studying triple negative breast cancer, thyroid tumors, ovarian cancer, and malignant pleural and peritoneal effusion. 15,17-20 IMS has the advantage of profiling a large number of biomarkers simultaneously. 21 It also requires only a small amount of tumor tissue (0.018 mm 2 per ROI; ~0.35 mm 2 in total on a single 6 ”m slide, per case, in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive proteomic research with MALDI MSI was performed by Casadonte et al [ 36 ] on pancreatic ductal adenocarcinoma and pancreatic neuroendocrine tumor tissues, leading to the development of a class prediction model to differentiate between both entities with high accuracy, essential for the appropriate treatment modality. MALDI MSI proteomic analyses has also proven their relevance in triple-negative breast cancer in the search for putative markers for recurrence-free survival: Phillips et al [ 37 ] identified nine proteins, not previously associated with breast cancer, that were significantly associated with worse recurrence-free survival when these proteins were highly expressed. Meding et al [ 38 ] demonstrated that MALDI MSI can be used to classify six different tumor entities in different organ sites with high confidence, based on 117 m / z species in the average imaging spectra.…”
Section: Maldi Mass Spectrometry Imaging In Cancer Researchmentioning
confidence: 99%